Executive summaries country profiles on food loss and waste - China, Colombia, Kenya and Vietnam - Axmann, H.B. (CGIAR Initiative on Low-Emission Food Systems, 2024)
In this document, we present an executive summary condensing the extensive Food Loss and Waste (FLW) country studies conducted by WFBR from 2022 to 2024, focusing on China, Colombia, Kenya, and Vietnam. Our synthesis of hotspot food products in these countries aims to guide the implementation of measures to reduce FLW. The quantifiable sums vary by product and chain stage. Concentrating efforts on food products and chain stages that significantly contribute to the earlier mentioned parameters can significantly enhance resource use efficiency. Simultaneously, this targeted approach aligns with climate mitigation efforts and promotes nutrition security. This integrated approach to FLW reduction therefor not only facilitates resource efficiency but also supports climate mitigation actions and nutrition security. Policymakers and other stakeholders in the food system can make informed decisions that contribute to multiple sustainability objectives simultaneously.